Tinjauan Hukum Islam terhadap Game Higgs Domino; Eksistensi, Legalitas, dan Transkasi Jual-Beli Chip - Alfiah Saad; Muhammad Adam HR; Fauziah Fauziah; Sappeami Sappeami; Bulkis Bulkis (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2025)
This study aims to examine the existence, legality, and chip trading transactions in the Higgs Domino game from the perspective of Islamic law. The game has rapidly gained popularity among Indonesian society in line with the advancement of digital technology and the rise of online entertainment culture. However, its popularity has raised concerns due to elements resembling gambling practices. This research is a qualitative library study using a normative legal approach. Primary sources include literature on fiqh muamalah and statutory regulations, while secondary sources consist of scientific journals and books published within the last ten years. The findings reveal that although Higgs Domino is legally available on digital platforms, its legality remains in a legal grey area due to weak regulations regarding digital forms of gambling, particularly in chip trading transactions. From the standpoint of Islamic law, these practices involve elements of gharar (uncertainty) and maisir (gambling), and lead to harmful social impacts such as addiction and wasteful spending. Therefore, Higgs Domino and all forms of chip transactions are deemed invalid under Islamic law and should not be legitimized within Muslim communities.